Different performance, full experience: a learning game applied throughout adulthood - Simon Greipl; Korbinian Moeller; Kristian Kiili; Manuel Ninaus (Serious Games Society, 2020)
Gaming may not primarily be associated with the elderly part of the population, but senior gamers represent a growing proportion. Evaluating the applicability of educational games across the lifespan is therefore crucial to better understand potential requirements in different domains and age groups. The current study applied a math learning game to participants from 19 to 79 years of age. We examined age-related differences along three domains: cognition, as measured by in-game performance, basic player experience with the game, and general player attitudes towards technology. Analyses of performance metrics related to speed clearly reflected an age-related decline, well in line with known effects from cognitive ageing. In contrast, error-metrics were associated with educational background. At the player experience level, however, we found no differences across the lifespan. All participants rated the game equally (positive). Furthermore, our results showed that attitudes towards technology only differed occasionally, for instance, senior participants seemed to be more technologically interested. Taken together, scoring systems as well as other in-game metrics based on performance, especially related to speed, should be adapted appropriately to player's age. Finally, elderly players' experience with the game and overall attitudes towards technology appeared comparable to other younger age groups.